Teaching speaking: challenges and solutions - Kovalova, Olena (My University, 2019)
Learning to speak is an important aspect of studying a foreign language. Language proficiency is determined by the level of speaking. However, students often have difficulties in mastering this aspect. The process of studying speaking is divided into several stages, which are considered in theses. Abstracts also offer kinds of tasks that help students learn to speak a foreign language.
Keywords: thesis; teaching speaking; conference materials; тези; навчання говоріння; матеріали конференції; кафедра ділової іноземної мови та міжнародної комунікації